The ones who got away - Loren, Roni (Loren, Roni. Ones who got away series, 2024)
"There were only a few survivors from that one fateful night. Now, twelve years later, the kids once called The Ones Who Got Away are back...and ready to claim the lives they never truly got to live. Liv Arias thought she'd never return to Long Acre High School--until a documentary brings her and the other survivors back home. Suddenly her old flame, Finn Dorsey, is closer than ever, and their attraction is still white-hot. When a searing kiss reignites their passion, Liv realizes this rough-around-the-edges man might be exactly what she needs."--